STRUGGLING MOTIVATION OF THREE INDONESIAN NOVICE WRITERS IN SCHOLARLY PUBLICATION - Fazalani, Runi; Saputra, Nanda; Desmita, Nina; Ningsih, Tri Zahra (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Writing for scholarly publication is commonly perceived as a daunting task in academic writing classes. Myriad studies have been geared to uncover theoretical significance within this process. However, little attention has been addressed in analyzing novice writers’ self- motivation construction in writing for scholarly publication. This present study was designed to investigate how self-motivation of research, writing, and publishing that emerged in the publication process encountered by Indonesian novice writers. Three Indonesian novice writers were involved based on previously set criteria. The data were elicited using a semi-structured interview and then analyzed descriptively. The results of this study indicated that the participants employed appealing attempts and that they were engaged in the complicatedness of writing for scholarly publication. These ways assisted them in sustaining their self-motivation in the publishing processes. Based on the findings, this study offers possible pedagogic attempts to help refine scholarly publication training, especially for novice writers in tertiary education.